Evaluation of endometrial natural killer cell expression of CD4, CD103, and CD16 cells in women with unexplained infertility. (September 2016) - Aksu, Sertan; Çalışkan, Eray; Cakiroglu, Yigit
Highlights: Successful pregnancy requires coordination between a receptive endometrium and the implanting blastocyst. It is reasonable to assume that some of the women with unexplained infertility have an endometrial factor that is contributing to their infertility. High numbers of endometrial natural killer cells may cause immune and vascular abnormalities in the endometrium of women with unexplained infertility. Abstract: Objective: To determine whether natural killer cell (NK) concentrations in the mid-secretory endometrial tissue of women with unexplained infertility differ from those in the mid-secretory endometrial tissue of fertile women. Methods: This study was conducted with 22 patients with unexplained infertility caused by unsuccessful ovulation induced with gonadotrophins and 12 healthy fertile women, who formed a control group. Mid-secretory endometrial tissue samples were obtained with a Pipelle catheter, and the endometrial NK cell phenotypes were determined by flow cytometry. Results: The median number of CD4+ cells in the endometrium was significantly lower in women with unexplained infertility compared with in the fertile controls (3.31 vs. 5.81; p = 0.02). The CD4 + /CD8 + cell ratio in the unexplained-infertility group was significantly lower than that in the control group (0.42 vs. 0.76, p = 0.01). The median number of CD103 + cells in the endometrium of the infertile group was significantly lower than that in the endometrium of the control group (4.40 vs. 6.73, p = 0.02). The median number of CD16 + cells was significantly higher in infertile women than in control women (0.12 vs. 0.001, p = 0.01). Conclusions: Significant reductions in the numbers of CD4 + and CD103 + cells as well as in the CD4 + /CD8 + ratio but an increased number of CD16 + cells in the endometrium of infertile women suggest that disordered NK cell activity may be a contributor to the etiology of unexplained infertility.